Parallel and Concurrent Programming with C++ Part 2. - Chiu Stone, Olivia; Stone, Barron (linkedin.com, 2020)
Explore advanced techniques for parallel and concurrent programming with C++. Learn about condition variables, semaphores, barriers, thread pools, and more.